2019
DOI: 10.1021/acs.jpclett.9b00599
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Metal Chloride for Minimizing the Halide Deficiency and Maximizing the Doping Efficiency in Mn(II)-Doped CsPbCl3 Nanocrystals

Abstract: Pretreatment using metal chlorides during the formation of halide deficient free perovskite nanocrystals is reported. Among several metal chlorides, Cu­(II)­Cl2 was observed to be ideal for the synthesis of highly emitting CsPbCl3 nanocrystals at high reaction temperature. Because high temperature remained more favorable for the dopant insertion, doping of Mn­(II) was carried out under this halide-rich system, and nearly 68% photoluminescence quantum yield was recorded. Analysis could not provide strong eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 47 publications
(70 reference statements)
2
84
0
Order By: Relevance
“…Therefore, CuCl 2 ‐assisted high‐temperature reaction minimize the chloride deficiency in the NCs, and hence, the PLQY is significantly enhanced in the as‐synthesized NCs. [ 216 ] Similarly, Wei et al. also noticed that the introduction of excess Cl − ions into CsPbCl 3 :Mn 2+ NCs can enhance the Mn 2+ PL intensity.…”
Section: Photoluminescence Modification Of Mn2+‐doped Halide Perovskitesmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, CuCl 2 ‐assisted high‐temperature reaction minimize the chloride deficiency in the NCs, and hence, the PLQY is significantly enhanced in the as‐synthesized NCs. [ 216 ] Similarly, Wei et al. also noticed that the introduction of excess Cl − ions into CsPbCl 3 :Mn 2+ NCs can enhance the Mn 2+ PL intensity.…”
Section: Photoluminescence Modification Of Mn2+‐doped Halide Perovskitesmentioning
confidence: 96%
“…It is reported that an excessive amount of Cl − ions is able to improve the emission intensity of Mn 2+ ‐doped 3D halide perovskites. [ 142,215–218 ] Lin et al. reported Mn 2+ ‐doped CsPbCl 3 NCs, using SiCl 4 as a promoting reagent in the synthesis process.…”
Section: Photoluminescence Modification Of Mn2+‐doped Halide Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some researchers reported the transition and alkaline earth metal ion doping into perovskite NCs. [12][13][14][15] For example, Belcher et al demonstrated for the rst time that partially substituting Pb 2+ by Co 2+ at the B-sites of the perovskite lattice was possible. 16 Sun et al had shown that the doping of CsPbX 3 NCs with Ni 2+ ions enabled single-color violet luminescence with near-unity PLQYs.…”
Section: Introductionmentioning
confidence: 99%